A multi-agent EPON emulator - Sadon S.K.; Din N.M.; Radzi N.A.; Yaacob M.; Rawi N.I.M.; Maier M.; Al-Mansoori M.H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Bandwidth; Fiber optic networks; Fiber to the x; Frequency allocation; Multi agent systems; Passive optical networks; Photonics; Quality of service; Distributed approaches; Dynamic bandwidth allocation; Emulator; EPON; Multi agent; Real-time traffic datum; Service delivery; Service differentiation; PROLOG (programming language)